Spatial distribution and evaluation of risk factors for bovine neosporosis in Rondônia, Brazil - Andrade, A. M.; Lopes, W. D.Z.; Felippelli, G. [UNESP]; Cruz, B. C. [UNESP]; Maciel, W. G. [UNESP]; Soares, V. E.; Ferreira, L. L.; Garcia, J. L.; Nino, B. S.L.; Minutti, A.; Rossi, G. A.M.; Jayme, V. S.; et al. (FapUNIFESP (SciELO), 2023)
Neospora caninum is an important worldwide parasite responsible for causing abortion in animals. Due to limited information on the occurrence of infection by this parasite in the state of Rondônia, Brazil, this study aimed to determine the seroprevalence and identify the risk factors associated with the infection in slaughtered cattle, from 19 municipalities distributed in seven microregions of the state. A total of 494 samples were obtained and subjected to anti-N. caninum antibodies, using the Indirect Immunofluorescence Reaction technique. Antibodies were detected in 5.06% (25/494) of the samples, in 30.30% (10/33) of farms, in nine municipalities located in four microregions of Rondônia. Of all the animals analyzed, 4.81% of the females (20/416) and 6.41% of the males (05/78) were seropositive for the parasite, with “abortion in the last 12 months” being considered an important risk factor for the occurrence of infection (OR = 9.54; p = 0.01). The present study points out the prevalence of anti-N. caninum antibodies in 5.06% of slaughtered animals and abortion as the main risk factor associated with infection by N. caninum, thus contributing to the elucidation of the epidemiology of this protozoan in Rondônia, Brazil
Distribuição espacial e avaliação dos fatores de risco para neosporose bovina em Rondônia, Brasil
Keywords: abortion; apicomplexa; IFAT; Neospora caninum; seroprevalence